PENGARUH UKURAN KOPERASI DAN JENIS KOPERASI TERHADAP KUALITAS SISTEM PENGENDALIAN INTERN (Studi Kasus pada Koperasi di Semarang) - Novrina Hasmawati; Rahardja Rahardja (Diponegoro Journal of Accounting, 2012)
The purpose of this research  was to determine whether the sizes of cooperative and cooperative types affect to the quality of the internal control system of cooperatives. This research  used  the cooperative sizes and the  types of cooperative as independent variables and the quality of the internal control system as the dependent variable. Cooperative sizes were seen from the number of turnover per year owned. Based on the turnover, the sizes of the cooperative were  divided into: the large cooperative,  the medium cooperative, and the small cooperative. While the types of cooperative were distinguished based on the common activities and economic interests, so that cooperatives can be divided into three types, namely; cooperative employee, savings and loan cooperative, and departemen of cooperative effort. The population of  this research  were  all the cooperatives that located in the Semarang City. The sample of  this research were 91 cooperatives using random sampling method. Hypothesis testing performed by descriptive statistical analysis. Statistical test results showed that the sizes of the cooperative took effect to the quality of internal control systems and the corporative types didn’t take effect to the quality of internal control systems . Testing of internal control system based on the size of cooperatives obtained chi-square  value 0,573 with a significance of 0,751 (above 0.05) it can be concluded that there was difference in the quality, between the cooperative system of internal control large, medium, and small. Testing for the internal control system based on the types of cooperatives obtained with a significance value of 60,084  chi-square 0.00 (under  0.05)and it can be  concluded that there was no difference in the quality of internal control system as seen from the types of cooperative.